Niue's Relationship of Free Association with new Zealand - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 1999)
This article provides an account of the relationship between Niue and New Zealand. Because Niue is both a self-governing state and one who has a relationship of free association with New Zealand, Niue's government makeup is both constitutional and contractual. The article discusses the principles of Niue's free association status with New Zealand in light of its constitutional makeup. The nature of the relationship between New Zealand and Niue is discussed in general terms, and the principles of economic and administrative assistance from New Zealand is explored in greater detail.